Recent Advances on Feasible Strategies for Monoterpenoid Production in Saccharomyces cerevisiae - Gao, Qiyu; Wang, Luan; Zhang, Maosen; Wei, Yongjun; Lin, Wei (Frontiers in Bioengineering and Biotechnology, 2020)
Terpenoids are a large diverse group of natural products which play important roles in plant metabolic activities. Monoterpenoids are the main components of plant essential oils and the active components of some traditional Chinese medicinal herbs. Some monoterpenoids are widely used in medicine, cosmetics and other industries, and they are mainly obtained by plant biomass extraction methods. These plant extraction methods have some problems, such as low efficiency, unstable quality, and high cost. Moreover, the monoterpenoid production from plant cannot satisfy the growing monoterpenoids demand. The development of metabolic engineering, protein engineering and synthetic biology provides an opportunity to produce large amounts of monoterpenoids eco-friendly using microbial cell factories. This mini-review covers current monoterpenoids production using Saccharomyces cerevisiae. The monoterpenoids biosynthetic pathways, engineering of key monoterpenoids biosynthetic enzymes, and current monoterpenoids production using S. cerevisiae were summarized. In the future, metabolically engineered S. cerevisiae may provide one possible green and sustainable strategy for monoterpenoids supply.